Painting with light : artistic experiments into the use of virtual reality as an animation production environment - Wastyn, Gert (2022)
While many researchers have examined the technical characteristics of using VR as a production environment for animation, its artistic potential has only sporadically been investigated. We want to contribute to this line of thought through reflection on a number of expanded animation workshops organized in the context of the Painting With Light project. In this paper we use flow theory in order to discuss the experience of using VR as a 3D prototyping tool. Our findings suggest that this practice can add an improvisatory and co-creative dimension to animation.